UJI KINERJA INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) RUMAH SAKIT DI KAYU PUTIH RAYA JAKARTA TIMUR - Gusvadillah Syarifudin; Ai Silmi; Mohamad Abdul Aziz (FT-USNI, 2022)
The hospital in the Pulomas area has built 2 units of Waste Water Treatment Plant facilities with Anaerobic-Aerobic Biofilter and Extended Aeration systems. The performance of Waste Water Treatment Plants (IPAL) requires comprehensive maintenance and evaluation of Waste Water Treatment Plants (IPAL) so that the waste water treatment system works optimally and reaches the quality standards set by the Government. The results of measurements carried out in Oct-Nov 2021 at the old WWTP show that the pH complies with the quality standards of Minister of Environment and Forestry Regulation P.68 of 2016, namely between 6-9. Meanwhile, the discharge measurement results have exceeded the permitted limit in accordance with the Waste Water Disposal Permit set by DPMPTSP DKI Jakarta, namely 29 m3/day, but the IPAL capacity is still capable of processing the average discharge generated. At the new IPAL with the same testing time, the results of measurements carried out in October-November 2021 showed that the pH was in accordance with the quality standards of Minister of Environment and Forestry Regulation P.68 of 2016, namely between 6-9. Meanwhile, the discharge measurement results are still below the permitted limit in accordance with the Waste Water Disposal Permit set by DPMPTSP DKI Jakarta, namely 20 m3/day. In the Old IPAL the COD parameter exceeds the permitted limit in accordance with the Waste Water Disposal Permit set by the DPMPTSP DKI Jakarta, namely 2.90 kg/day, whereas in the new IPAL the evaluation results can be seen that there is no processing in the pramary treatment, namely a grease trap with processing efficiency. of 0%. From the results of the evaluation that has been carried out, it can be concluded that the average processing efficiency of the Old IPAL is 51.28%. When compared with the standard criteria for a WWTP with an Anaerobic-Aerobic Biofilter system with a processing efficiency level of 90-95%, the performance of the Old WWTP is less than optimal. Meanwhile, the average processing efficiency of the New IPAL is 46.74%. When compared with the standard criteria for a WWTP with an Extended Aeration system, the processing efficiency level is 85-87%, then the performance of the New WWTP is also less than optimal.